2005
DOI: 10.1111/j.1365-2591.2005.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical characterization and the influence of cyclic loading on the behaviour of nickel‐titanium wires employed in the manufacture of rotary endodontic instruments

Abstract: The mechanical behaviour of the NiTi wires was modified slightly by cyclic tensile loading in the superelastic plateau. As the changes tended towards stabilization, the clinical use of rotary NiTi ProFile instruments does not compromise their superelastic properties until they fracture by fatigue or torsional overload, or are otherwise discarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 22 publications
5
28
0
4
Order By: Relevance
“…In fact, the values for FlexMaster, EndoSequence, Hero, and ProFile were 56.2, 56.0, 55.4, and 54.6 Ni %wt, respectively. These values were close to those (56 wt% Ni, 44 wt% Ti) reported previously (1,(13)(14)(15)(16)(17). These values are within the nominal composition range specified in the ASTM standards for wrought NiTi alloys used in medical devices and surgical implants (F2063-05 2005).…”
Section: Discussionsupporting
confidence: 87%
“…In fact, the values for FlexMaster, EndoSequence, Hero, and ProFile were 56.2, 56.0, 55.4, and 54.6 Ni %wt, respectively. These values were close to those (56 wt% Ni, 44 wt% Ti) reported previously (1,(13)(14)(15)(16)(17). These values are within the nominal composition range specified in the ASTM standards for wrought NiTi alloys used in medical devices and surgical implants (F2063-05 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Although there is a strong relationship between the maximum torque an instrument can withstand and its diameter (27,28), the torsional behavior of rotary NiTi instruments is also affected by a variety of other factors, including taper, design, chemical composition of alloy, and thermomechanical processes applied during manufacturing (21,29,30). The cross-sectional configuration, in particular, has been shown to affect the stress distribution pattern of the instrument in both torsion and bending (8-11, 22, 31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Berutti et al (39) found that rotary NiTi instruments worked better at high torque, speculating that the auto-reverse function at low torque may result in unnecessarily stored stress thus reducing the instrument's useful life. Similarly, Bahia et al (100) found that an accumulation of internal stresses did not produce unfavorable changes in the superelastic properties of NiTi but will eventually lead to fatigue failure of the instruments. Yared et al (36,101) observed that high torque was safe for experienced operators and that novices would benefit most from low-torque controlled motors.…”
Section: Dynamics Of Instrument Usementioning
confidence: 97%